PENGETAHUAN DAN SIKAP TENTANG PERAWATAN PAYUDARA DALAM MENCEGAH KEJADIAN BENDUNGAN ASI PADA IBU NIFAS DI WILAYAH KERJA PUSKESMAS MOJOSARI TAHUN 2024 - Ika Yuni Susanti; Dyah Siwi Hety (HOSPITAL MAJAPAHIT : JURNAL ILMIAH KESEHATAN POLITEKNIK KESEHATAN MOJOKERTO, 2024)
One of the predisposing factors for failure to achieve exclusive breastfeeding is that the baby does not get enough breast milk due to problems in breastfeeding due to the mother experiencing engorgement. The purpose of this study was to determine the relationship between knowledge and attitudes about breast care and the occurrence of engorgement in postpartum mothers. This study used an analytic correlation research method with a cross sectional approach. This research was conducted at the Mojosari Community Health Center, Mojokerto Regency in March to May 2024. The population was all postpartum mothers on days 1-6, a sample of 58 respondents was taken using an accidental sampling technique. The results of the study 58 respondents obtained postpartum mothers who had less knowledge 31 respondents (53.4%) breast milk dams 23 respondents (39.7%), enough 17 respondents (29.3%) engorgement 9 respondents (15.5%), good 10 respondents (17.2%) dam ASI 3 respondents (5.2%). Meanwhile, for postpartum mothers, 35 respondents (60.3%) had a positive attitude toward breastfeeding, 17 respondents (29.3%), and postpartum mothers had a negative attitude, 23 respondents (39.7%), 18 respondents (30.0%). From the results of the Chi-Square test, the relationship between knowledge and the incidence of ASI dams obtained a value of p = 0.035, while the relationship between attitude and the incidence of ASI dams obtained a value of p = 0.024 so that p <0.05, it can be concluded that H1 is accepted, which means that there is a relationship between knowledge and attitudes towards the ASI dam incident at the Mojosari Community Health Center, Mojokerto Regency. Based on the results of the study, education and attitudes of postpartum mothers can affect breast care that is carried out properly and regularly so that it can reduce the incidence of engorgement in postpartum mothers and facilitate breast milk production